Purification By Oligo(dT)-Cellulose of Viral-Specific RNA from Sarcoma Virus-Transformed Mammalian Nonproducer Cells - Scolnick, Edward M. (1973)
Viral-specific RNA has been purified by oligo(dT)-cellulose chromatography from sarcoma virus-transformed nonproducer cells. This RNA comprises approximately 3% of the purified RNA, as judged by RNA-DNA hybridization.